Tax Planning on The Multinational Companies in Indonesia - Novita, Wellia; Rahmi Fahmy (Asean International Journal of Business, 2022)
The discussion of this review is motivated by the problems of multinational companies, especially in Australia, America and Indonesia, which prefer tax planning efforts with Tax avoidance. The purpose of this paper is knowledge of tax planning in multinational companies that occur as a result of business transactions. The results of the discussion prove that each country carries out tax avoidance using 2 (two) measurements, namely the Effective Tax Rate (ETR) and Book Tax Differences (BTD). This writing describes the reasons why business people do tax planning by tax avoidance, which can be explained, namely: 1) Tax laws that cannot be obeyed by companies and provide high costs in fulfilling them. 2) The value of the tax payable becomes large due to the process of calculation errors and deposits as well as tax reporting. 3) The company feels that it is necessary to do tax planning in order to implement tax obligations and fulfill the tax provisions that have been determined, so as not to invite suspicion from tax inspectors, 4) Good public morals in tax reporting. Finally, it is suggested to the readers that the scope of this paper is in accordance with the cases that occurred in several reviewed journals, hopefully it will provide benefits and positive contributions. 4) Good community morale in tax reporting. Finally, it is suggested to the readers that the scope of this paper is in accordance with the cases that occurred in several reviewed journals, hopefully it will provide benefits and positive contributions. 4) Good community morale in tax reporting.